Flow boiling of dilute emulsions. (December 2017) - Janssen, D.; Kulacki, F.A.
Highlights: Measurement of heat transfer in flow boiling of dilute emulsions of FC-72 and pentane in water. Stable flow boiling for droplet concentrations of 0.1–2% with droplets of 5 to 7 microns. Enhancement of heat transfer coefficient is up to 60% depending on total mass flux concentration. Enhanced heat transfer coefficients obtained without a large penalty on the pumping requirement. Abstract: Measurements of heat transfer coefficients are presented for flow boiling of a dilute emulsion in meso-scale channel flow. The emulsions comprises droplets of FC-72 and pentane in water at a droplet concentration of one percent or less by volume. Droplet size is on the order of 5–10 μm. The experimental apparatus comprises a bottom heated flat channel with a gap height of 0.25 mm and constant wall heat flux of 10–50 W/cm 2 . Mass flux is held constant at ∼100 kg/m 2 s. Heat transfer coefficients are enhanced on the order of 20–60% when the wall temperature exceeds the saturation temperature of the dilute component but is less than the saturation temperature of the carrier fluid. This increase is attributed to agitation due to the liquid-vapor transition of the suspended component. As the wall temperature approaches the saturation temperature of the carrier fluid, boiling of it commences, and heat transfer coefficients increase dramatically as in single-component flow boiling. Thus, the emulsion exhibits more desirable heat transfer characteristics across the spectrum from single-phase through two-phase flow. At very low heat flux, there is little to no differentiation of heat transfer coefficients of carrier fluid alone and that of the emulsion because the droplets require a degree of superheat before evaporating. The present results provide a useful experiential framework for categorizing flow boiling conditions associated with dilute emulsions and complement existing data on pool boiling.